Dysregulated miRNAome and Proteome of PPRV Infected Goat PBMCs Reveal a Coordinated Immune Response - Khanduri, Alok; Sahu, Amit Ranjan; Wani, Sajad Ahmad; Khan, Raja Ishaq Nabi; Pandey, Aruna; Saxena, Shikha; Malla, Waseem Akram; Mondal, Piyali; Rajak, Kaushal Kishor; Muthuchelvan, D.; Mishra, Bina; Sahoo, Aditya P.; et al. (Frontiers in Immunology, 2018)
In this study, the miRNAome and proteome of virulent Peste des petits ruminants virus (PPRV) infected goat peripheral blood mononuclear cells (PBMCs) were analyzed. The identified differentially expressed miRNAs (DEmiRNAs) were found to govern genes that modulate immune response based on the proteome data. The top ten significantly enriched immune response processes were found to be governed by 98 genes. The top ten DEmiRNAs governing these 98 genes were identified based on the number of genes governed by them. Out of these 10 DEmiRNAs, 7 were upregulated and 3 were downregulated. These include miR-664, miR-2311, miR-2897, miR-484, miR-2440, miR-3533, miR-574, miR-210, miR-21-5p and miR-30. miR-664 and miR-484 with proviral and antiviral activities, respectively, were upregulated in PPRV infected PBMCs. miR-210 that inhibits apoptosis was downregulated. miR-21-5p that decreases the sensitivity of cells to the antiviral activity of IFNs and miR-30b that inhibits antigen processing and presentation by primary macrophages were downregulated, indicative of a strong host response to PPRV infection. miR-21-5p was found to be inhibited on IPA upstream regulatory analysis of RNA-sequencing data. This miRNA that was also highly downregulated and was found to govern 16 immune response genes in the proteome data was selected for functional validation vis-a-vis TGFBR2 (TGF-beta receptor type-2). TGFBR2 that regulates cell differentiation and involved in several immune response pathways was found to be governed by most of the identified immune modulating DEmiRNAs. The decreased luciferase activity in Dual Luciferase Reporter Assay indicated specific binding of miR-21-5p and miR-484 to their target thus establishing specific binding of the miRNAs to their targets.This is the first report on the miRNAome and proteome of virulent PPRV infected goat PBMCs.